النفط وحروب التغيير في العلاقات الدولية (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The research started from the importance of the role played by oil in international relations and the extent of the readiness of the major countries to carry out wars and crises in the world to maintain their interests in general and the continuity of the receipt of oil under the conditions appropriate to their economies in particular, which was shown through the study which adopted the descriptive analytical approach to reach to the importance of oil for these countries and the historical tracking of wars and crises since the discovery of oil and try to reach one of the most important reasons is to maintain oil production and full control over oil reserves outside its borders, especially in the Middle East Area with the brain Which resulted in a series of events that were represented by the so-called "Arab spring revolutions." This is what the researcher expressed in the wars of change that aim to change the political systems that exist under several of names, including changing dictatorial regimes, Or to rid the region of terrorism or weapons of mass destruction and others, in a sense more accurate calculations of the military operations that occur in the Arab region and the Middle East, but they all follow the economic and political interests of the major countries, led by the United States of America, this what was mentioned by the researcher through the findings.  انطلق البحث من أهمية الدور الذي يلعبه النفط في العلاقات الدولية وما مقدار استعداد الدول الكبرى للقيام بحروب وأزمات على مستوى العالم للحفاظ على مصالحها بشكل عام واستمرارية ورود النفط بالشروط المناسبة لاقتصادياتها بشكل خاص، وهو الأمر الذي تبين من خلال اجراء الدراسة التي اعتمدت المنهج الوصفي التحليلي للتوصل إلى أهمية النفط بالنسبة لهذه الدول والتتبع التاريخي للحروب والأزمات منذ اكتشاف النفط ومحاولة التوصل لأحد أهم أسبابها المتمثل بالحفاظ على انتاج النفط والهيمنة التامة على الاحتياطيات النفطية خارج حدودها خاصة في منطقة الشرق الأوسط ذات المخزون الضخم، ومنخفض التكلفة وهو الأمر الذي نتج عنه مجموعة من الأحداث تمثلت بما يسمى" ثورات الربيع العربي " وهو ما عبر عنه الباحث بحروب التغيير التي تهدف إلى إحداث تغيير في الأنظمة السياسية الموجودة تحت مسميات عدة منها تغيير أنظمة دكتاتورية أو تحرير الشعوب أو لأهداف حقوق الانسان أو لتخليص المنطقة من الارهاب أو من أسلحة الدمار الشامل وغيرها،  بمعنى أدق تتعدد الحسابات للعمليات العسكرية التي تحدث في المنطقة العربية  والشرق الأوسط إلا أنها جميعا تتبع للمصالح الاقتصادية والسياسية للدول الكبرى وعلى رأسها الولايات المتحدة الأمريكية وهذا ما جسده الباحث من خلال النتائج التي توصل إليها.